2020
DOI: 10.21511/ppm.18(1).2020.39
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-security effect on organizational internal process: mediating role of technological infrastructure

Abstract: Adopting the technologies among organizations comes with the continuous worries of protection and hacking. The idea of cyber-security has become over the years the main interest of many organizations, which depend on technologies in its operations, which requires them to pay extra attention to their technological infrastructure. The current study aims at examining the influence of cyber-security forces on organizational internal operations and the role of technological infrastructure in defining and controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…, 2022), competitive analyses within the financial sector (Nisa et al. , 2022), risk management strategies (Khaw and Teoh, 2023) and the exploration of interventions targeting consumer behavior (Reisch et al. , 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022), competitive analyses within the financial sector (Nisa et al. , 2022), risk management strategies (Khaw and Teoh, 2023) and the exploration of interventions targeting consumer behavior (Reisch et al. , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Hasan et al (2021) revealed that a mature IT infrastructure enhances an organization's ability to counter cyber-attacks. Kilani (2020) identified that cybersecurity factors such as data growth, technology expansion and operational control indirectly impact an organization's cybersecurity strategies, while data growth was the most significant motivator. However, technological factors can also pose challenges for organizations.…”
Section: Thematic Framework Of Cybersecuritymentioning
confidence: 99%
“…Moreover, Kilani (2020) provides insights into the indirect effects of cyber-security motivators on internal processes within an organization, emphasizing the importance of cyber-security readiness in shaping organizational processes. This supports the evaluation of the relationship between an organization's readiness to combat cyber-attacks and its security performance/adoption.…”
Section: Literature Reviewmentioning
confidence: 99%